Mental health of intimate partner violence victims: depression, anxiety, and life satisfaction - Maka Lortkipanidze; Nino Javakhishvili; Seth J. Schwartz (Frontiers in Psychology)
ObjectiveMost research on intimate partner violence emphasizes physical and sexual abuse, often overlooking the distinct impacts of different forms of violence on mental health. Psychological abuse is often treated as a single category, overlooking important subtypes like verbal-emotional abuse and controlling behaviors, while economic abuse remains understudied despite its potential impact on well-being. Additionally, life satisfaction—a key indicator of psychological health—is rarely examined alongside depression and anxiety, and the distinction between depressive symptoms and anxiety is often unclear in studies on intimate partner violence. This study addresses these gaps by examining the specific effects of five forms of abuse—physical, sexual, economic, dominance-isolation, and emotional-verbal—on depression, anxiety, and life satisfaction among 293 women survivors of intimate partner violence in Georgia. It also investigates the mediating role of anxiety in the relationship between intimate partner violence and depressive symptoms, thereby focusing on the distinct and unique characteristics of these two mental health outcomes.ResultsThe findings revealed that participants commonly experienced at least four forms of intimate partner violence simultaneously, which was associated with adverse mental health outcomes. The impact of intimate partner violence varied by type: physical and sexual abuse were linked to reduced life satisfaction and increased anxiety but were not significant predictors of depressive symptoms. In contrast, dominance-isolation—one form of psychological abuse—predicted depressive symptoms and anxiety but did not affect life satisfaction. Furthermore, anxiety functioned as a mediator in the relationship between physical and sexual intimate partner violence and depressive symptoms, offering insights into the mechanisms underlying the development of depression in abused women.ConclusionIn conclusion, this study emphasizes the complex relationship between various forms of intimate partner violence and mental health, particularly focusing on the mediating role of anxiety in the development of depressive symptoms. The findings highlight the critical need for the development of comprehensive, culturally sensitive intervention strategies aimed at intimate partner violence victim women, especially those who have endured multiple types of abuse. These interventions should be designed to address the specific mental health challenges associated with diverse forms of interpersonal partner violence, as well as the socio-cultural contexts in which victims reside.